Architecture and information retrieval: an approach of the Integrated System for Academic Management (SIGA) at Eduardo Mondlane University - Macie, Gildo Carlos [UNESP]; Nascimento, Natalia Marinho do [UNESP]; Madio, Telma Campanha de Carvalho [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2024)
The architecture and retrieval of academic and pedagogical information through the Integrated Academic Management System are addressed with the aim of understanding the efficiency of the system in responding to the demands of students and lecturers at the School of Communication and Arts of the Eduardo Mondlane University (Mozambique), based on the analysis of its architecture. The study is qualitative in its approach and exploratory-descriptive in its objectives, having been operationalized by bibliographic and documentary research for the purposes of theoretical basis, as well as through an approach to the system based on documents that allowed obtaining specific information on the subject in question. It was found that when developing the first versions of the system, little attention was paid to the type of user, the system interfaces were uninviting and the wrong language was used for certain resources, creating dissatisfaction, frustration, or embarrassment for the user to find the desired information to satisfy his or her demands. Furthermore, when the system was used at peak times, such as the beginning and at the end of academic semesters, this system was not able to respond to demands with the necessary quality and speed. However, the introduction of this system is considered a great advance for the institution, taking into account the challenges posed by Information and Communication Technologies. The system needs to be continually improved in terms of architecture, in order to increasingly facilitate information retrieval and the inclusion of users with special needs, which is one of the great expectations generated with the implementation of the new version 2.0.
Keywords: information; information architecture; information retrieval; SIGA; UEM